PEMBATALAN AKTA HIBAH ATAS HARTA BERSAMA DALAM PERKAWINAN (STUDI PUTUSAN PENGADILAN NEGERI MEDAN NO.425/PDT.G/2012/PN.MDN) - DIAN PADENA HARAHAP (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Sunarmi2. Saidin3. T. Keizerina Devi A The results of the research showed that the grant sourced from joint without spouse’s approval is an act against positive law. Grant provision must not violate the subjective rights of both parties. The annulment of the deed of such grant is also an object imperfection because it does not fully belong to the grant provider it is an object of dispute over joint property. It is proven by the ruling handed down by the Judges who annul the grant deed made by Defendant II against the grant provided by Defendant I to Defendant II that has violated the provisions in article 1320 of the Civil Code, particularly related to a cause in which there was not any reason that can be explained of providing the grant, and related to halal cause that can be explained that it has violated the Plaintiff as the legal wife of Defendant I as she has the right over their joint property.Keywords: Joint Property, Grant and Annulment of Grant Certificate